THE IMPACT OF ENGLISH SONGS TO IMPROVING ON ENGLISH LISTENING SKILLS - Anisa Mailawati; Anita Anita (Journal of Research on Language Education, 2022)
Songs have an impact that is either bad or good in language learning. The purpose of this study is to determine the impact of songs on language learning, especially in improving listening skills. The data were collected through questionnaires. In analyzing the collected data, a quantitative research method was employed. The study found that the use of songs can have a good impact and is likely to improve students' listening comprehension skills